Preserving what is valued : museums, conservation, and First Nations - Clavir, Miriam, 1948- (UBC Museum of Anthropology Research publication., 2002)
What are the "right ways" to preserve heritage? Are the aims and purposes of museums necessarily at odds with those of First Nations? This thoughtful book explores the concept of museum conservation in light of cultural repatriation issues, and helps readers understand the complex relationship between museums and Aboriginal peoples.